Characteristics of secondary caries lesion around composite resin restorations - Berenice Barbachan e Silva; Débora Heller; Marisa Maltz (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2010)
The aim of this study was to analyze the features of secondary caries and their relationship with the presence of restorations marginal defects as gap, negative ledge (NL, lack of restorative material) and positive ledge (PL, overhang). Eighty proximal surfaces of Class II resin restorations were photographed and analyzed using a stereomicroscope (X40). It was recorded the presence of external secondary caries, gap, NL, PL and after the restorations removal, the presence of internal lesion. All the exams were done in 10 well-defined points. The reproducibility (Kappa Index) of the exams of external caries, presence of gaps, restorations marginal defects and internal caries were, respectively: 0.88 e 0.94; 0.80 e 0.87; 0.83 e 0.90 e 0.82 e 0.94. As reprodutibilidades (Kappa) dos exames de cárie externa, EDR, presença de degraus e cárie interna no início e depois da análise de 50% da amostra foram, respectivamente: 0,88 e 0,94; 0,80 e 0,87; 0,83 e 0,90 e 0,82 e 0,94. The prevalence of secondary caries (p < 0.05) and gap (p < 0.01) were associated with gingival margin. The restorations marginal defects (NL and PL) were not associated with any specific location (buccal, lingual or gingival) (p= 0.073). It was observed a relationship between these defects with secondary caries prevalence (gap: p= 0.004; NL and PL: p= 0.017). This association could be explained by the biofilm accumulation usually observed in the interface tooth surface/ restoration marginal defects. The presence of internal lesion was associated with external lesion (p< 0.001). Although, in 141 points was observed internal lesion without the presence of external lesion. The majority of these lesions showed internal enamel involvement. Only 8% had demineralization restricted to dentine, which could suggest residual caries. The results of this study showed that secondary caries lesion frequently began externally on the interface tooth/restoration, where diagnose, control and arrestment of the lesions is possible.